Making amends atonement in morality, law, and politics - Radzik, Linda, 1970- (Oxford : Oxford University Press, 2009)
Can wrongs be righted? Or does the impossibility of changing the past mean that we remain permanently guilty? While atonement is usually considered a theological topic, this book uses the resources of secular moral philosophy to explore the possibility of correcting the wrongs we do to one another.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Responsibility; Atonement; Reparation (Criminal justice); Restitution; Reconciliation; Restorative justice; Penance